The dependence of intergrain damageability of casting on the technological treatment route - Кусий, Ярослав Маркіянович; Кузін, Олег Анатолійович; Кузін, Микола Олегович (Eastern-European Journal of Enterprise Technologies, 2016)
The study determines the role of heredity varieties in machining and assembling the products. The paper presents an analysis of interdependence between technological heredity, the stages of a product life cycle, and structural features of the surface layer. It emphasizes the importance of taking into account procurement operations in analyzing the impact of technological heredity on the parameters of a product. We have analyzed modern concepts for assessing damageability of materials and products and suggested the method of LM-firmness to analyze and assess the transformation of inhomogeneous surface layers of the cast samples into technological damage during machining. We have experimentally studied the role of technological surface treatment in damage formation and processed the findings. We used the model of functionally-graded structure of grain boundaries to determine the role of the cutting modes in the formation of structural stress concentrators. The devised method for determining the Weibull homogeneity coefficient (m) on the surface of the cast billets allows prognoses of the damage development in the surface layers after machining. The most rational technological treatment route for the casting of AD-type alloys comprises two successive finishing millings, and the Weibull homogeneity coefficient increases by 26-84% compared to the starting workpiece due to a lower damage of the material at the stage of finishing milling.